Response of a Number of Gas Exchange Variables to Aerobic Physical Exertion of Varying Intensity Children Aged (10-12) Years - Omar Al-Naqeeb (College of Physical Education and Sport Sciences, 2021)
Identify the differences in the variables (relative oxygen consumption volume (V̇O2), relative carbon dioxide volume (V̇CO2), respiratory exchange ratio (RER), and metabolic equivalent (METs)) when moving from rest to physical aerobic exertion of increasing intensity in children aged ( 10-12) years old, and The researchers hypothesized statistically significant differences in the variables (relative oxygen consumption volume (V̇O2), relative volume of carbon dioxide (V )CO2), respiratory exchange ratio (RER), metabolic equivalent (METs)) when moving from rest to aerobic physical exertion of gradient intensity In children aged (10-12) years. The two researchers used the descriptive approach in a comparative style for its suitability and the nature of the study, as for the research sample, it consisted of (10) children of (10-12) years of age from primary school students in the (Al-Jawadin) primary school for the academic year (2019-2020) from Diwaniyah governorate, The final experiment was conducted under a condition of moderate ambient temperature (22°C ± 1) and humidity ranging (20-30%) on the research sample in complete rest and during physical exertion gradient using the Bruce protocol to reach the maximum oxygen consumption (air voltage with gradient intensity) in Physiology Lab at the College of Physical Education and Sports Sciences / University of Al-Qadisiyah, and to process the data, the researcher used the following statistical methods to arrive at the results (arithmetic mean, standard deviation, coefficient of variation, body mass index, body surface area, and variance analysis using repeated measurements). The researchers reached the following conclusions: